2008
DOI: 10.1111/j.1939-7445.2006.tb00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Harvesting in an Age-Class Model With Age-Specific Mortalities: An Example From Namibian Linefishing

Abstract: ABSTRACT. . Namibia's main linefish species, the kob, is subject to age‐specific fishing mortalities that differ for the two fisheries (commercial linefishing vessels and recreational anglers) exploiting it. The study finds that the planning horizon is crucial when determining the most profitable allocation of kob resources between the two fisheries. With a short planning period, it is optimal to allocate much of the catch to commercial fishing. However, if a longer planning period is used, it is preferable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In contrast to the continuous time-infinite number of cohorts framework [12], this study applies an approach that is directly related to the successful numerical optimization studies [5,17,19,20,42] and the policy analysis papers [1,4,39,40]. In spite of endogenous recruitment, harvesting cost, and economic nonlinearities, the model is a transparent nonlinear programming problem (Section 2).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to the continuous time-infinite number of cohorts framework [12], this study applies an approach that is directly related to the successful numerical optimization studies [5,17,19,20,42] and the policy analysis papers [1,4,39,40]. In spite of endogenous recruitment, harvesting cost, and economic nonlinearities, the model is a transparent nonlinear programming problem (Section 2).…”
Section: Introductionmentioning
confidence: 98%
“…Hannesson [17] employed a Beverton-Holt [3] type of multicohort (exogenous recruitment) model and showed numerically that optimal harvesting takes the form of pulse fishing for North Atlantic cod. Recently, Stage [42] applied an age-structured model to Namibian linefishing. Bjö rndal and Brasao [5] studied East Atlantic bluefin tuna fisheries and found support for a strong recovery program as well as for eliminating part of the gear due to adverse effects on population age structure.…”
Section: Introductionmentioning
confidence: 99%
“…Bottleneck signatures were stronger in the SWC stock, which could be a reflection of differential fishing pressure in this region by certain fisheries such as gillnet (Hutchings and Lamberth, 2003). In Namibia, the impact of commercial fisheries is in contrast to recreational fisheries because different demographic fractions of the local stock are targeted by each fishery type, respectively (Stage, 2006). However, among other limitations of such tests, the power of detecting population bottlenecks can be hampered by low number of markers and sample sizes (8-9 loci and 31-38 individuals) (Peery et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although after Hannesson and Clark et al many other papers have found, by using numerical methods, that pulse fishing is the optimal policy in some fisheries modelled with Beverton-Holt models (Horwood, 1987;Bjørndal and Brasão, 2006;Bjørndal et al 2004aBjørndal et al , 2004bStage, 2006; Da Rocha et al, 2012), the first analytical results were only recently derived. Tahvonen (2009), proves that in a 2-age structured fisheries model with endogenous recruitment and harvesting costs, optimal harvesting consists of pulse fishing under specific conditions such as nonselective gear.…”
Section: Introductionmentioning
confidence: 99%